Complete mitochondrial genomes and phylogenetic relationships of two Saussurella species (Orthoptera: Tetrigidae) from China - Caili Teng; Yuemei Li; Yazhen Chen; Weian Deng (Mitochondrial DNA. Part B. Resources)
The complete mitochondrial genomes of Saussurella cornuta (Haan, 1843) and Saussurella longiptera (Yin, 1984) were sequenced and analyzed. The circular mitogenomes of S. cornuta and S. longiptera are 16,531 bp and 16,313 bp in length, respectively. The nucleotide compositions are significantly biased toward AT, with AT contents of 69.9% in S. cornuta and 72.2% in S. longiptera. Phylogenetic analysis reveals that S. longiptera represents the earliest branching species within the genus Saussurella, with Saussurella borneensis and S. cornuta forming a sister group. These mitochondrial genomes are provide valuable insights for studying the systematics of Saussurella.